Menggambar Bebas Sebagai Upaya Mengurangi Perilaku Insecure Pada Anak Usia Dini - Arini Inayatul Fajriyah; Arri Handayani; Dini Rakhmawati (Departement of Mathematics Education, 2024)
Basically, insecurity is related to standards set by someone in dialogue with themselves, such as family or peers. Then a feeling of unease develops when a person compares himself to others in a way that is considered negative, or not in accordance with society's order of life. Therefore, this will become a problem in early childhood development, which will have an impact on the child's life. The aim of this research is to understand a problem in early childhood and as an effort to prevent the impact of this problem, and to be able to provide appropriate food. Therefore, as parents and educators, you must know and see your child's growth and development. The focus of this research consists of (1) To understand the personality of children who behave insecurely, (2) the efforts of parents or educators in dealing with children who behave insecurely.